PENGARUH PENAMBAHAN LAKASE DARI JAMUR TIRAM PUTIH (Pleurotus ostreatus) TERHADAP AKTIVITAS ANTIOKSIDAN TEH HIJAU [Effect of The Addition of Laccase from White Oyster Mushroom (Pleurotus ostreatus) Towards Antioxidant Activity of Green Tea] - Tagor M. Siregar; A. Herry Cahyana; Natalia , (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2012)
Laccase is one of the enzymes that can be used in organic synthesis using aromatic compounds (polyphenols and aminofenol) as substrates. Polyphenol compound in green tea is flavan-3-ols or catechin which are susceptible to enzymatic reaction with laccase. In this research laccase isolated from white oyster mushroom was added into the green tea extract. Addition of laccase is expected to yield products with a higher antioxidant activity. Prior to it’s use, laccase activity was determined and had a specific activity of 0.54 Unit/mg. The green tea extract was prepared using methanol and water as solvents. The antioxidant activity was evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging activity method and the total flavonoid content was assayed by spectrophotometry. Antioxidant compounds are identified by using UV-Vis spectrophotometry and GC-MS. Addition of laccase into green tea extract resulted in precipitates showing a significant increase in flavonoid content and antioxidant activity. Use of methanol as solvent resulted in extract with higher antioxidant activity and total flavonoid than that extracted with water. Qualitative analysis with spectrophotometer UV-Vis and GC-MS showed that the new components in the precipitates were a variety of dimeric products with increased molecular weight and antioxidant activity. Addition of laccase into green tea extract has yielded products with higher antioxidant activity.